2016
DOI: 10.1186/s12879-016-1910-7
|View full text |Cite
|
Sign up to set email alerts
|

A case report of a cystic fibrosis patient with repeated isolation of Trichosporon mycotoxinivorans identified by a novel short-extraction method

Abstract: Background Trichosporon mycotoxinivorans is a recently described yeast-like fungal organism and its association as a pathogen for patients with cystic fibrosis (CF) was reported previously. We show the clinical course of a CF patient over 9 years as well as the applications of modern molecular and proteomic identification techniques of this rare fungus.Case presentationWe present the case of a 32-year-old male CF patient with sputum cultures continuously positive with the anamorphic yeast T. mycotoxinivorans d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…In our previous study (Peng et al, 2019), the sensitivity of the GMU1709 strain to antifungal drugs was determined using the commercial method ATB FUNGUS 3, and our results indicated that the A. mycotoxinivorans GMU1709 strain is sensitive to the antifungal drugs, including several triazoles, flucytosine, and amphotericin B. Notably, amphotericin B also exhibits high efficacy in treating A. mycotoxinivorans GMU1709 infection in our previous study (Peng et al, 2019), which is in contrast with previous clinical reports (Hickey et al, 2009;Goldenberger et al, 2016). Here, we further detected the genes possibly involved in antifungal drug resistance in the GMU1709, CICC 1454, and ACCC 20271 strains based on MARDy (Nash et al, 2018).…”
Section: Genes Putatively Involved In Antibiotic Resistancecontrasting
confidence: 85%
See 1 more Smart Citation
“…In our previous study (Peng et al, 2019), the sensitivity of the GMU1709 strain to antifungal drugs was determined using the commercial method ATB FUNGUS 3, and our results indicated that the A. mycotoxinivorans GMU1709 strain is sensitive to the antifungal drugs, including several triazoles, flucytosine, and amphotericin B. Notably, amphotericin B also exhibits high efficacy in treating A. mycotoxinivorans GMU1709 infection in our previous study (Peng et al, 2019), which is in contrast with previous clinical reports (Hickey et al, 2009;Goldenberger et al, 2016). Here, we further detected the genes possibly involved in antifungal drug resistance in the GMU1709, CICC 1454, and ACCC 20271 strains based on MARDy (Nash et al, 2018).…”
Section: Genes Putatively Involved In Antibiotic Resistancecontrasting
confidence: 85%
“…Later, Hirschi et al (2012) reported the first case of disseminated fungal co-infection caused by A. mycotoxinivorans and another fungus, which emerged after liver and lung transplantation in a patient with cystic fibrosis. Subsequently, a case series of chronic A. mycotoxinivorans infection has been reported in patients with cystic fibrosis (Shah et al, 2014;Goldenberger et al, 2016). Unlike previous studies, Dabas et al (2017) reported the emergence of A. mycotoxinivorans in three cases of bloodstream infections in a retrospective study.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, this microorganism has been related to deep-seated infections in immunocompromised patients with invasive disposals in India (17). The use of Bruker's MALDI-TOF MS as a reliable tool for A. mycotoxinivorans species identification has helped strengthen the epidemiologic link of T. mycotoxinivorans to cystic fibrosis (18,19). Thus, it appears that inclusion of the species in the database used for clinical diagnosis is now mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that this microorganism may not be simply a coloniser of the respiratory tract of CF patients. Indeed, among eight well-documented cases of non-immunosuppressed CF patients reported with positive respiratory samples for T. mycotoxinivorans ( A. mycotoxinivorans ) ( Supplementary data , Table), six showed a decline in lung function after the first positive culture ( Kröner et al 2013 , Shah et al 2014 , Goldenberger et al 2016 , Muñiz et al 2016 ). Consolidating our case with the information provided by the literature review summarised above, we suggest that T. mycotoxinivorans ( A. mycotoxinivorans ) may colonise and infect the respiratory tract of CF patients, causing progressive deterioration of their lung function.…”
mentioning
confidence: 99%